Utility of Underwater Weenie Life Forms as Voluminous Organisms: A Review - Rout George Kerry; Samprit Padhiary; Gyana Prakash Mahapatra; Jyoti Ranjan Rout (Marine Science Department Diponegoro University, 2018)
Coral reefs are a sundry subaqueous ecological community, combined with the calcium carbonate structures secreted by converting the carbon dioxide present in the water into limestone. The biotic portion of the coral reef is marine animal known as polyps that have resemblance with jellyfish. Unlike terrestrial environment, the marine component is tightly interdependent. Taking out one component or loss of from a system can have a devastating impact or undermine the entire marine ecosystem. Reefs specifically are a vital organism among underwater life which is dependent on corals and provide key microhabitat, shelter and breeding ground for thousands of species of fish, crustaceans, mollusks, etc. Coral reef possesses vital ethnobotanical properties, which cures asthma, arthritis, and even cancer. Apart from medicinal properties, further it provides 2/3rd of oxygen on earth. However, the destructive fishing practices, pollution and ocean acidification have endangered this kingdom and have led to the threatening of the entire fabric of the underwater life. As human beings are also dependent up to much extent for centuries, there is a high probability of being severely affected if the coral reef extinct leaving the seabed barren. Corals cover almost 1 % of the oceans present on earth, but the irony is 75 % of them are on a verge of extinction. Therefore, the present review focuses on its conservation, cultivation and significance of their application in the field of biomedical science.Keywords: Coral reef, endangered, ethnobotany, extinction, marine ecosystem, pollution.